Procedura analizy skupień z wykorzystaniem programu komputerowego clusterSim i środowiska R - Walesiak, Marek (Cluster Analysis Procedure with ClusterSim Computer Programme and E Environment, 2008)
The first part of the article presents major steps in a cluster analysis procedure (see [Milligan 1996, 342-343; Walesiak 2005]). The next part presents the functions of clusterSim, stats, cluster, and ade4 packages of R environment which are applied to solving clustering problems in each stage of this procedure. Also the examples of the syntax (procedures) for solving different clustering problems are presented. These procedures help to resolve a broad range of classification problems that are not available in statistical packages (e.g. SPSS, Statistica, S-Plus, SAS).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 44-56